KORELASI UKURAN-UKURAN TUBUH DAN VOLUME AMBING DENGAN PRODUKSI SUSU KAMBING PERANAKAN ETAWAH DI KECAMATAN METRO TIMUR - Wahyu Puji Santoso, M Dima Iqbal Hamdani, Arif Qisthon, and Sulastri (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This research aimed to determine the relationship between body measurements including body length (x1), body height (x2), chest circumference (x3), and udder volume (before milking (x4)) with milk production of Etawah Crossbreed goat at the Mandiri Jaya Bersama and Yosomukti farms, Metro Timur District from July-August 2019. This study used a survey method with twenty female Etawah Cross Breed goats as samples taken by purposive sampling. Data were analyzed using correlation and linear regression analysis. The results showed that volume of udder before milking has a strong relationship (r = 0.82) with milk production, with regression line equation Ŷ = 109,65+0,82X4 (R2 = 0.66). Each of body length (r = 0,09), body height (r = 0,09), or chest circumference (r = 0,18) variables were very low correlated with milk production. Combination variables of body length, body height, chest circumference, and udder volume before milking had a strong correlation with milk production, with r = 0.832 and the regression line equation of Ŷ = 172,457-16,322X1+5,414X2+8,361X3+0,845X4 (R2 = 0.68). It can be concluded that volume of udder before milking can be used in the estimation of milk production of Etawah Crossbreed goat. Keywords: Etawah Crossbreed, Correlation, Regression, Body measurements, Milk production